First‐in‐Asian Phase I Study of the Anti‐Fibroblast Growth Factor 23 Monoclonal Antibody, Burosumab: Safety and Pharmacodynamics in Adults With X‐linked Hypophosphatemia. (14th September 2018) - Cheong, Hae Il; Yoo, Han‐Wook; Adachi, Masanori; Tanaka, Hiroyuki; Fujiwara, Ikuma; Hasegawa, Yukihiro; Harada, Daisuke; Sugimoto, Maiko; Okada, Yosuke; Kato, Masaki; Shimazaki, Ryutaro; Ozono, Keiichi; et al.
ABSTRACT: X‐linked hypophosphatemia (XLH) is a disease caused by abnormally elevated FGF23 levels, which cause persistent hypophosphatemia accompanied by subsequent reduction in bone mineralization that presents as rickets or osteomalacia. Burosumab is a fully human monoclonal antibody targeting FGF23 that is under development for the treatment of FGF23‐related hypophosphatemia including XLH. The safety, tolerability, and proof of concept of burosumab have been evaluated in patients with XLH in previous studies conducted in countries outside of Asia. The objective of this study was to evaluate the safety, tolerability, pharmacokinetics (PK), pharmacodynamics (PD), and expression of anti‐drug antibodies in Japanese and Korean adults with XLH. This was a multicenter, sequential dose‐escalation, open‐label, single‐dose study. This study began with cohort 1 (s.c. dose of burosumab 0.3 mg/kg), after which the dose was escalated sequentially in cohort 2 (s.c. dose of burosumab 0.6 mg/kg) and cohort 3 (s.c. dose of burosumab 1.0 mg/kg). The PK of burosumab were linear within the dose range of 0.3 to 1.0 mg/kg. The PD effects such as serum phosphorus concentration, serum 1, 25[OH]2 D3 concentration, and ratio of tubular maximum reabsorption rate of phosphate to glomerular filtration rate (TmP/GFR) were elevated after a single s.c. administration. The area under the receiver‐operating characteristic curve from 0 to t (AUC0–t ) values calculated using the change from baseline values of serum phosphorus, serum 1, 25(OH)2 D3, and TmP/GFR were correlated with the AUC0–t of burosumab. Furthermore, no serious adverse events (AEs), deaths, remarkable increase or decrease in the corrected calcium or intact PTH levels, or signs of nephrocalcinosis or its worsening were observed after treatment. Some AEs and drug‐related AEs were observed; however, there were no clinically meaningful tendencies. The positive effects and acceptable safety profile seen in this study are encouraging for Japanese and Korean patients with XLH. © 2018 The Authors JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.